Hemifacial Spasm Secondary to Parotid Pleomorphic Adenoma With Stylomastoid Foramen Extension. Issue 1 (January 2017) - Martin, Eliot J.; Carlson, Matthew L.; Moore, Eric J.; Jackson, Ryan S.
Abstract : Objective: To report hemifacial spasm (HFS) as a rare presenting symptom of a benign parotid neoplasm involving the stylomastoid foramen. Methods: Case report with literature review. Results: An 18-year-old woman presented with a 1-year history of a progressively enlarging right infra-auricular mass with new onset ipsilateral severe HFS. Clinical vetting unveiled a palpable 2 cm, firm, minimally mobile mass medial to the angle of the mandible. Imaging revealed a heterogeneous intraparotid mass with tumor extension into the stylomastoid foramen. Diagnostic consideration was given to neurogenic tumors and neoplasms of parotid origin. The patient ultimately underwent superficial parotidectomy and the tumor was found superficial and extrinsic to the proximal facial nerve trunk but extended into the stylomastoid foramen. The tumor was removed after performing mastoidectomy with mastoid segment facial nerve decompression. Frozen section pathology was consistent with pleomorphic adenoma. Postoperatively the patient had normal facial nerve function with immediate and complete resolution of HFS. To date there are only three other published reports of benign parotid tumors presenting with HFS and this is the first illustrating intratemporal tumor extension. Conclusions: HFS is a rare presenting symptom associated with benign parotid neoplasms with scarce documentation in the literature. In this index case, tumor extirpation with mastoid segment facial nerve decompression provided immediate and durable resolution of symptoms.